2020
DOI: 10.1038/s41467-020-18809-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced polymer mechanical degradation through mechanochemically unveiled lactonization

Abstract: The mechanical degradation of polymers is typically limited to a single chain scission per triggering chain stretching event, and the loss of stress transfer that results from the scission limits the extent of degradation that can be achieved. Here, we report that the mechanically triggered ring-opening of a [4.2.0]bicyclooctene (BCOE) mechanophore sets up a delayed, force-free cascade lactonization that results in chain scission. Delayed chain scission allows many eventual scission events to be initiated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 55 publications
1
55
0
Order By: Relevance
“…15). For instance, gem-dihalocyclopropane mechanophores, reported by Craig's group, [123][124][125][126][127] generate a 2,3-dihaloalkene sequence after activation as shown in Fig. 15a.…”
Section: Mechanocatalystsmentioning
confidence: 98%
“…15). For instance, gem-dihalocyclopropane mechanophores, reported by Craig's group, [123][124][125][126][127] generate a 2,3-dihaloalkene sequence after activation as shown in Fig. 15a.…”
Section: Mechanocatalystsmentioning
confidence: 98%
“…15,16 Subsequently, the Craig group reported a clever alternative design of a tetrasubstituted [4.2.0]bicyclooctene based mechanophore that, upon mechanochemical ring-opening into 1,3-cyclooctadiene, can spontaneously undergo intramolecular lactonization and result in backbone cleavage (Scheme 1C). 17 These recent examples showcased mechanically enhanced polymer degradation as a new modality of response, but in these designs, the hydrolysable functionalities already exist in the polymers before mechanoactivation. As a result, deleterious hydrolysis prior to the desired mechanoactivation would inevitably hydrolyze these same functionalities in the precursor polymers and change their properties, leading to the generation of undesired scissile cyclobutane linkages or premature polymer cleavage that disrupts the transduction of force and thus limits the extent of mechanoactivation.…”
Section: Introductionmentioning
confidence: 99%
“…c) Reproduced with permission under the terms of the Creative Commons license. [ 48 ] Copyright 2020, The Authors. Published by Springer Nature.…”
Section: Activation Of Mechanophores By Smfsmentioning
confidence: 99%
“…The authors reported the mechanical activation of a new mechanophore based on [4.2.0] bicyclooctene (BCOE) (Figure 5c). [ 48 ] Several copolymers of BCOE, g DCC‐COD, and epoxy‐COD were prepared. All the synthesized copolymers had 14 mol% of BCOE.…”
Section: Activation Of Mechanophores By Smfsmentioning
confidence: 99%